Design and develop AR app for Changi Jewel HSBC Vortex - Shafiqah Athirah Binte Ramli (Nanyang Technological University, 2022)
As the advancement of hardware and software applications exponentially grows, augmented reality (AR) and virtual reality (VR) can now be called as mixed reality (MR). MR provides the ability to interact with digital data and the real world in the same context and time frame. The author has developed a mobile based MR application for the National Library. This report will cover the investigation and analysis of AR, VR and MR. In addition, it will also cover the design and development of the AR mobile application, which focuses on delivering fun and interactive videos and models. On top of that, the report will also include the development process of constructing videos, photos, and models using C# scripts for running the application. A 3D model of the nasi lemak was also created for future use.